2019
DOI: 10.1074/jbc.ra118.007222
|View full text |Cite
|
Sign up to set email alerts
|

The role of liquid–liquid phase separation in aggregation of the TDP-43 low-complexity domain

Abstract: Pathological aggregation of the transactive response DNAbinding protein of 43 kDa (TDP-43) is associated with several neurodegenerative disorders, including ALS, frontotemporal dementia, chronic traumatic encephalopathy, and Alzheimer's disease. TDP-43 aggregation appears to be largely driven by its low-complexity domain (LCD), which also has a high propensity to undergo liquid-liquid phase separation (LLPS). However, the mechanism of TDP-43 LCD pathological aggregation and, most importantly, the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
319
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(344 citation statements)
references
References 67 publications
22
319
3
Order By: Relevance
“…The observed correlation between stability and zeta potential also has important pathophysiological implications, specifically for the transition of condensates from their liquid state to solid aggregates. It has been shown that FUS can transition into toxic aggregates associated with the onset and development of motor neuron disease more readily when it is contained in condensates (8), and this trend holds true for other proteins as well, including TDP-43 and other condensate forming systems (38,39). Recent theoretical work has also highlighted how condensates could behave as compartments for aggregate formation, and has even indicated how more aggregates could form within condensates of greater size (40).…”
Section: Discussionmentioning
confidence: 99%
“…The observed correlation between stability and zeta potential also has important pathophysiological implications, specifically for the transition of condensates from their liquid state to solid aggregates. It has been shown that FUS can transition into toxic aggregates associated with the onset and development of motor neuron disease more readily when it is contained in condensates (8), and this trend holds true for other proteins as well, including TDP-43 and other condensate forming systems (38,39). Recent theoretical work has also highlighted how condensates could behave as compartments for aggregate formation, and has even indicated how more aggregates could form within condensates of greater size (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, TDP-43 aggregates are also observed -albeit at low frequency -in control samples 36 and, in vitro, TDP-43 can form both amyloid aggregates and liquid condensates [37][38][39][40][41] . Mutations in TDP-43 cause ~5% of familial ALS cases 17,42 , with these…”
Section: Main Textmentioning
confidence: 95%
“…TDP-43 aggregates are also present at autopsy in nearly all cases of frontotemporal dementia (FTD) that lack tau-containing inclusions (about half of all cases of FTD which is the second most common dementia) 33 . TDP-43 aggregates are also a hallmark of inclusion body myopathy and a secondary pathology in Alzheimer's, Parkinson's, and Huntington's disease [33][34][35] .However, TDP-43 aggregates are also observed -albeit at low frequency -in control samples 36 and, in vitro, TDP-43 can form both amyloid aggregates and liquid condensates [37][38][39][40][41] . Mutations in TDP-43 cause ~5% of familial ALS cases 17,42 , with these…”
mentioning
confidence: 99%
“…Furthermore, limited observations indicate that tau LLPS may also occur in neurons (14). Because the environment inside phase separated droplets is distinct from that of the surrounding aqueous phase, LLPS may have a major effect on the formation of pathological protein aggregates in AD and other neurodegenerative disorders (17)(18)(19)(20).…”
mentioning
confidence: 99%